Estimation of procurement costs incurred by public customers: a case study of a Russian region. Issue 1 (5th March 2018) - Yakovlev, Andrei; Balaeva, Olga; Tkachenko, Andrey
Abstract : Purpose: This paper aims to measure the cost of procurement because public procurement procedures prescribed by legislation not only enhance transparency and competition but also entail certain transaction costs for both customers and suppliers. Design/methodology/approach: These costs are important to the efficiency of the procurement system. However, very few previous studies have focused on estimating procurement costs. This paper proposes a methodology for public procurement cost evaluation. Findings: This paper shows how procurement costs can be calculated using a formalized survey of public customers. This methodology was tested with a representative group of public customers operating in one region of the Russian Federation. Originality/value: The authors formulate the policy implications of this paper, as they relate to the improvement of public procurement regulations and argue that this methodological approach can be applied in other developing and transitioning economies.